2012
DOI: 10.1097/qai.0b013e318264460f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HIV-1 Ambiguous Nucleotide Frequency During Antiretroviral Treatment Interruption

Abstract: Nucleotide mixtures in HIV-1 population sequences reflect sequence diversity. We evaluated gag and pol ambiguous nucleotide frequencies during an analytic treatment interruption (ATI) in an HIV-1 therapeutic vaccine study. The proportion of ambiguous nucleotides was significantly higher at ATI week 16 than at either the time of first detectable viremia (P<0.001 gag and P=0.03 RT) or pre-antiretroviral therapy (P=0.007 gag). No significant differences were observed in the proportion of ambiguous nucleotides bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The general picture, however, was that therapeutic vaccination did not result in positive selection increasing viral diversity, similar to what others reported [3,7]. Although Li et al [7] observed an increase in ambiguous bases resulting in increased epitope diversity after therapeutic vaccination, this was also found in placebo controls. Hoffmann et al…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The general picture, however, was that therapeutic vaccination did not result in positive selection increasing viral diversity, similar to what others reported [3,7]. Although Li et al [7] observed an increase in ambiguous bases resulting in increased epitope diversity after therapeutic vaccination, this was also found in placebo controls. Hoffmann et al…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, in one DC-TRN participant studied in detail, immune escape from Rev-specific immune pressure was observed in a newly defined CTL epitope [32]. The general picture, however, was that therapeutic vaccination did not result in positive selection increasing viral diversity, similar to what others reported [3,7]. Although Li et al [7] observed an increase in ambiguous bases resulting in increased epitope diversity after therapeutic vaccination, this was also found in placebo controls.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Genetic diversity may result in ambiguous calls (also referred to as mixtures) in the reported sequence, so that a signal of within-patient genetic diversity is retained even though there is only a single sequence per patient. We use the ambiguous calls to quantify within-patient genetic diversity (see Figure 1BE, grey box), following several other studies [17][18][19][20]. Although ambiguous calls are an imperfect measure of diversity, it has been shown that the signal from ambiguous calls can be reproduced between laboratories [21].…”
Section: Introductionmentioning
confidence: 99%